Sistem Pendukung Keputusan Pemilihan Instruktur Fitness Menerapkam Metode Analitycal Hierarchy Process - Munthe, Ketrin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Tama GYM is a place to exercise with a location in the field, which is comfortable and environmentally friendly. The trainer place is quite spacious and is trained by professional instructors at a very affordable entrance price. Fitness instructor is someone who serves as a guide and gives instructions to individuals or groups of people who guide members, to assist members in achieving goals based on physical health, both in physical fitness and body shape appearance by routinely doing fitness. Fitness instructors are usually called sports guides, nowadays many young people and parents are very fond of this sport. In the process of accepting Fitness Instructors, it is still done manually, namely by inputting prospective instructor data in the book so that negligence often occurs among TAMA GYM employees. The owners of TAMA GYM so far have only seen from the appearance of the Fitness Instructor itself, even though in the process of receiving Fitness Instructors must use several criteria. The criteria used in this information are appearance, character, experience, achievement and age. The AHP method is one of the methods used to solve this problem. From the research, the best alternative results fell to A9 on behalf of